BETON ASPAL BUTON EPURE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Asphalt concrete mixture consists of course aggregates, fine aggregates, filler and bitumen. These materials are composed according to grading limits to produce a job mix formula. It has followed quality requirements. Buton epure is a mixture of asphalt and filler of extract Buton rock asphalt. This material can be employed as a binder of asphalt concrete mixtures. Due to material characteristic, the mixture composition should be corrected by its specific gravity. There is model of asphalt concrete mixture using Buton epure. From this research indicates that Buton epure can be employed as a kind of binder of asphalt concrete. Buton epure 55P with 5 % additive, creates an asphalt concrete mixture followed Bina Marga Superpave, and also closed to Bina Marga standard.